2008
DOI: 10.1128/iai.01688-07
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Secretion Promotes Enterohemorrhagic Escherichia coli Adherence and Intestinal Colonization

Abstract: Enterohemorrhagic Escherichia coli (EHEC) is a noninvasive food-borne pathogen that colonizes the distal ileum and colon. Proteins encoded in the EHEC locus of enterocyte effacement (LEE) pathogenicity island are known to contribute to this pathogen's adherence to epithelial cells and intestinal colonization. The role of non-LEE-encoded proteins in these processes is not as clear. We found that the Z2053 gene (designated adfO here), a gene located in a cryptic EHEC prophage, exhibits similarity to adherence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 65 publications
1
55
2
Order By: Relevance
“…Mutation of etpC, the first gene in the etp operon, has been shown to result in a significant reduction of O157 : H7 colonization in an infant rabbit model of disease (Ho et al, 2008). In this study, two effectors of type II secretion previously suggested to contribute to adherence, StcE (Grys et al, 2005) and AdfO (Ho et al, 2008), were upregulated in TW14359.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Mutation of etpC, the first gene in the etp operon, has been shown to result in a significant reduction of O157 : H7 colonization in an infant rabbit model of disease (Ho et al, 2008). In this study, two effectors of type II secretion previously suggested to contribute to adherence, StcE (Grys et al, 2005) and AdfO (Ho et al, 2008), were upregulated in TW14359.…”
Section: Discussionmentioning
confidence: 62%
“…Mutation of etpC, the first gene in the etp operon, has been shown to result in a significant reduction of O157 : H7 colonization in an infant rabbit model of disease (Ho et al, 2008). In this study, two effectors of type II secretion previously suggested to contribute to adherence, StcE (Grys et al, 2005) and AdfO (Ho et al, 2008), were upregulated in TW14359. The StcE metalloprotease, the expression of which is positively influenced by Ler (Lathem et al, 2002), is hypothesized to promote adherence by cleaving proteins in the glycocalyx and mucin layers atop the intestinal epithelium, facilitating close contact with the intestinal mucosa (Grys et al, 2005).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In addition to being a conduit for transport of secreted effector proteins, the EspA filament of the LEE-encoded T3SS has also been implicated in adherence of EPEC strains (103). Additionally, the EHEC virulence plasmid pO157 encodes the Etp T2SS along with YodA and StcE, two Etp-secreted factors that influence adhesion processes (228,259). yodA mutants of EHEC demonstrate reduced adherence to HeLa cells and are less competitive for colonization of the rabbit intestine (259).…”
Section: Adherence To Gastrointestinal Epitheliummentioning
confidence: 99%